Cytosolic alkalinization in guard cells: an intriguing but interesting event during stomatal closure that merits further validation of its importance - Bharath, Pulimamidi; Gahir, Shashibhushan; Raghavendra, Agepati S. (Frontiers in Plant Science, 2024)
Stomatal closure is essential to conserve water and prevent microbial entry into leaves.Alkalinization of guard cells is common during closure by factors such as abscisic acid, methyl jasmonate, and even darkness. Despite reports pointing at the role of cytosolic pH, there have been doubts about whether the guard cell pH change is a cause for stomatal closure or an associated event, as changes in membrane potential or ion flux can modulate the pH. However, the importance of cytosolic alkalinization is strongly supported by the ability of externally added weak acids to restrict stomatal closure. Using genetically encoded pH sensors has confirmed the rise in pH to precede the elevation of Ca 2+ levels. Yet some reports claim that the rise in pH follows the increase in ROS or Ca 2+ . We propose a feedback interaction among the rise in pH or ROS or Ca 2+ to explain the contrasting opinions on the positioning of pH rise. Stomatal closure and guard cell pH changes are compromised in mutants deficient in vacuolar H + -ATPase (V-ATPase), indicating the importance of V-ATPase in promoting stomatal closure. Thus, cytosolic pH change in guard cells can be related to the rise in ROS and Ca 2+ , leading to stomatal closure. We emphasize that cytosolic pH in stomatal guard cells deserves further attention and evaluation.